2023
DOI: 10.52711/0974-360x.2023.00084
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Precise, and Sensitive RP-HPLC Method for Quantification of Teneligliptin Hydrobromide and Metformin Hydrochloride: Development and Validation

Abstract: Simple, rapid, sensitive, robust, and validated reverse phase- high-performance liquid chromatography RP_(HPLC) was developed for the quantification of anti-diabetic drugs Teneligliptin hydrobromide (TH) and Metformin hydrochloride (MH) in bulk and in formulation. The RP-HPLC method was developed using an HPLC system with a PDA detector. A simple, accurate and cost-effective gradient approach is used by using C18 Inertsil ODS (150×4.6)mm, 5µ. A method was developed and validated as per ICH Q2 (R1) guideline. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A review of the existing literature focusing on the quantitative analysis of TGT and PGZ indicated that efforts have been directed toward devising analytical methods for these individual drugs, as well as in combination with other medications. These efforts have resulted in developing various methods including UV spectroscopy [3,[12][13][14][15], HPLC [2,3,7,[16][17][18][19][20][21][22][23], high-performance thin-layer chromatography (HPTLC) [15,[24][25][26][27][28][29], and LC-MS [23,[30][31][32][33][34][35][36]. Among the various methods that have been reported, the work by Gheewala et al in 2017 provided a comprehensive account of simultaneously determining TGT and PGZ within a synthetic mixture using both UV spectroscopy and HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature focusing on the quantitative analysis of TGT and PGZ indicated that efforts have been directed toward devising analytical methods for these individual drugs, as well as in combination with other medications. These efforts have resulted in developing various methods including UV spectroscopy [3,[12][13][14][15], HPLC [2,3,7,[16][17][18][19][20][21][22][23], high-performance thin-layer chromatography (HPTLC) [15,[24][25][26][27][28][29], and LC-MS [23,[30][31][32][33][34][35][36]. Among the various methods that have been reported, the work by Gheewala et al in 2017 provided a comprehensive account of simultaneously determining TGT and PGZ within a synthetic mixture using both UV spectroscopy and HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of literature reveals numerous analytical approaches for the determination of TEN, both as an individual compound and in combination with concurrently administered medications. These methods include UV spectrophotometry [1][2][3], highperformance liquid chromatography (HPLC) [4][5][6][7][8][9], and high-performance thin-layer chromatography (HPTLC) [10][11][12]. Conversely, PIO, whether as a single drug or in combination with other coadministered drugs, has been previously evaluated through diverse methodologies, including UV spectrophotometry [13,14], HPLC [15][16][17][18][19][20][21][22][23][24][25][26] and HPTLC [27,28] .…”
Section: Introductionmentioning
confidence: 99%